Analysis of Potassium Content and Dietary Fiber in Crispy Cookies Subtituted with Breadfruit Flour (Artocarpus communis) and Red Bean Flour (Phaseolus vulgaris L.) As An Alternative Snack for Hypertention Patients - Aysya Aiz Annisa' (Bachelor Nutrition Study Program - Faculty of Medicine, 2025)
The prevalence of hypertension in Indonesia has shows an increasing trend, from 25.8% in Riskesdas 2013 to 34.1% in Riskesdas 2018. Modification of daily food intake patterns has become one of the most component lifestyle changes in reducing blood pressure. Adequate intake of potassium and dietary fiber is highly recommended for the prevention of high blood pressure. This study aims to determine the potassium and dietary fiber content in crispy cookies made with a substitution of red bean flour and breadfruit flour as an alternative snack for hypertensive patients. The research design used is a quasi-experimental approach with a Completely Randomized Design (CRD). The crispy cookie formulations consisted of four variations of red bean flour and breadfruit flour ratios: F0 (0 gr: 0 gr), F1 (10 gr: 70 gr), F2 (20 gr: 60 gr), and F3 (30 gr: 50 gr). Data analysis was performed using descriptive statistics. The results show that the average potassium content ranged from 275.47 to 407.81 mg, and the dietary fiber content ranged from 6.83% to 12.05%. The selected formulation was F3, with potassium content of 407.81 mg and dietary fiber of 11.84%. Based on these results, the recommended serving size for one consumption is 50 gr (10 pieces).